Social housing and urban renewal : a cross-national perspective - Watt, Paul, 1969-; Smets, Peer (Emerald Publishing Limited, 2017)
This book offers a cross-national perspective on contemporary urban renewal in relation to social rental housing. Social housing estates - as developed either by governments (public housing) or not-for-profit agencies (housing associations) - emerged out of post-war urban renewal programmes and became a prominent feature of the landscape across North American, European and Australian cities. During the last two decades, however, Western governments have launched high-profile 'new urban renewal' programmes whose aim has been to change the image and status of these estates away from that of being zones of concentrated poverty and other social problems. This latest phase of renewal has involved demolishing many social housing estates and replacing them with mixed-tenure housing developments in which deconcentration of poverty and the social mixing of poor tenants and wealthy homeowners are major goals.